PENGARUH ZAKAT PRODUKTIF BAZNAS KOTA MEDAN TERHADAP PERTUMBUHAN USAHA DAN KESEJAHTERAAN MUSTAHIK DI KECAMATAN MEDAN TIMUR - Dewi Sundari Tanjung (Universitas Islam Negeri Sumatera Utara, 2019)
The purpose of this study was to determine the effect of Zakat, Infaq and Productive Sadaqah on the growth of micro enterprises and mustahiq welfare in Medan City, and also to determine the effect of the growth of micro mustahiq businesses on mustahiq welfare in Medan City. This study belongs to the explanatory or confirmatory research category, which is to get an explanation of the relationships between variables. The object to be investigated / analyzed is the variable productive Islamic charity (ZIS) with micro-business variables and welfare variables mustahik on the Medan BAZDA. This research is a quantitative research that uses an analysis of the SPSS approach. The results showed that Zakat, Infaq and Productive Sadaqah had an effect on the growth of mustahiq micro enterprises in Medan City, whereas Zakat, Infaq and Productive Sadaqah did not affect the welfare of mustahiq in Medan City. The potential of ZIS in Medan City is actually quite large, if they distribute their zakat through the BAZNAS in Medan City, a larger fund will be collected for the benefit of the ummah.